Change in the ovarian environment after hysterectomy with bilateral salpingectomy: is it the technique or surgery itself?. (September 2016) - Atalay, M.A.; Cetinkaya Demir, B.; Ozerkan, K.
Abstract: Objective: To compare the effects of total laparoscopic hysterectomy with bilateral salpingectomy (TLH-BS) and total abdominal hysterectomy with bilateral salpingectomy (TAH-BS) on ovarian function among women of reproductive age. Study design: One hundred and three patients with a diagnosis of benign uterine disorder were divided into two groups in this prospective longitudinal study. Patients who had never had sexual intercourse and patients with uterovaginal disproportion underwent TAH-BS ( n  = 57), and the remaining patients ( n  = 46) underwent TLH-BS. Ovarian function was assessed before and 6 months after surgery; ovarian volume was assessed by gray-scale ultrasonography, and levels of serum follicle-stimulating hormone (FSH), luteinizing hormone (LH), oestradiol (E2), anti-Mullerian hormone (AMH) and inhibin B were measured. Results: Postoperative serum FSH, LH and inhibin B decreased significantly in both groups. Postoperative serum E2 did not change significantly. Postoperative serum AMH and ovarian volume decreased significantly in the TAH-BS group ( p  = 0.016 and p  < 0.001, respectively), but not in the TLH-BS group. Significant differences were observed between the TLH-BS and TAH-BS groups with respect to change in FSH ( p  = 0.012) and ovarian volume ( p  = 0.001); between-group differences were not significant for changes in AMH and inhibin B. Conclusions: Although serum AMH did not change significantly in patients who underwent TLH-BS, ovarian aging commenced following both surgical procedures.